1988
DOI: 10.1093/infdis/158.2.349
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Clostridium difficile Colonization in Newborns: Results Using a Bacteriophage and Bacteriocin Typing System

Abstract: We used a typing system based on bacteriophage and bacteriocin susceptibility to study the epidemiology of Clostridium difficile colonization of newborn infants. C. difficile was found in the stools of 30 (16.0%) of 187 infants who were screened. Increased length of stay in the nursery (P less than .001) and delivery by cesarian section (P less than .001) were associated with higher rates of colonization. The isolates initially detected from the environment and the infants were strain B1811-1700. Strain B1537/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…This result is consistent with those of previous studies in European and North-American countries, where asymptomatic carriage rates in infants under 2 years of age were found to be high, varying from 24 to 75 % (Bacon et al, 1988;Brazier, 1998;Collignon et al, 1993;Matsuki et al, 2005;Rexach et al, 2006;Tullus et al, 1989;Yamamoto-Osaki et al, 1994). The great variability observed in carriage rates corresponds to the 0-1 year period, while at the age of 2 years, colonization is about 37-46 % regardless of the study (Collignon et al, 1993;Matsuki et al, 2005;Torres et al, 1984;Yamamoto-Osaki et al, 1994).…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with those of previous studies in European and North-American countries, where asymptomatic carriage rates in infants under 2 years of age were found to be high, varying from 24 to 75 % (Bacon et al, 1988;Brazier, 1998;Collignon et al, 1993;Matsuki et al, 2005;Rexach et al, 2006;Tullus et al, 1989;Yamamoto-Osaki et al, 1994). The great variability observed in carriage rates corresponds to the 0-1 year period, while at the age of 2 years, colonization is about 37-46 % regardless of the study (Collignon et al, 1993;Matsuki et al, 2005;Torres et al, 1984;Yamamoto-Osaki et al, 1994).…”
Section: Discussionsupporting
confidence: 93%
“…Leukocytosis is a common clinical feature in the severely ill patient, with leukocyte counts exceeding 15,000 cells per mm3 in 40 to 50% of patients (196,262 (34,35,73,118,153,178,228,252,258); however, other studies have reported acquisition rates of 0 to 6% (127,153,246,257). These differences in the acquisition rates of C. difficile in neonates and young children most likely represent varied degrees of environmental exposure in nurseries or transfer from the hands of hospital staff rather than disparities in the rate of maternal exposure (12). Prevalence of the carrier state has made it difficult to assess the relationship between C. difficile colonization and disease in this age group (57).…”
Section: Introductionmentioning
confidence: 99%
“…The high carriage rate in infancy has been ascribed to the low capacity of the infantile gut microbiota to suppress the growth of C. difficile. Colonization rates are increased in bottle-fed and caesarean section-delivered infants (14)(15)(16); in the latter case, carriage is probably dependent on delayed acquisition of suppressive anaerobes (17). A significant portion of C. difficile strains colonizing infants are toxin producers (13), but the vast majority of colonized infants have no overt symptoms.…”
mentioning
confidence: 99%